«La società non esiste». Il Novecento di Francesco Pecoraro - Davo, Michela (L'ospite ingrato, 2024)
Through the works of Francesco Pecoraro, which reflect its outcomes and ambivalences, the essay tries to retrace some of the social, political and economic changes that marked the twentieth century: the progressive emptying of the public dimension (evident in the representation of spaces), the high rate of conflict (particularly strong on a generational scale), a pervasive sense of catastrophe.